Dissection flap fenestration can reduce re-apposition force of the false lumen in type-B aortic dissection: a computational and bench study - Ahuja, Aashish; Guo, Xiaomei; Noblet, Jillian N.; Krieger, Joshua F.; Roeder, Blayne; Haulon, Stéphan; Chambers, Sean; Kassab, Ghassan (Frontiers in Bioengineering and Biotechnology, 2024)
Thoracic endovascular aortic repair (TEVAR) has been widely adopted as a standard for treating complicated acute and high-risk uncomplicated Stanford Type-B aortic dissections. The treatment redirects the blood flow towards the true lumen by covering the proximal dissection tear which promotes sealing of the false lumen. Despite advances in TEVAR, over 30% of Type-B dissection patients require additional interventions. This is primarily due to the presence of a persistent patent false lumen post-TEVAR that could potentially enlarge over time. We propose a novel technique, called slit fenestration pattern creation, which reduces the forces for re-apposition of the dissection flap (i.e., increase the compliance of the flap). We compute the optimal slit fenestration design using a virtual design of experiment (DOE) and demonstrate its effectiveness in reducing the re-apposition forces through computational simulations and benchtop experiments using porcine aortas. The findings suggest this potential therapy can drastically reduce the radial loading required to re-appose a dissected flap against the aortic wall to ensure reconstitution of the aortic wall (remodeling).. new aneurysm formation is present in 60% of patients, and freedom from reintervention stands at only 40% (Fattori, et al. 2013). Several factors have been linked to long-term aortic growth after type-B dissection, namely, the persistence of FL perfusion from distal re-entry tears, absence of either multiple entries or distal re-entry (Trimarchi, et al. 2014). Complete re-apposition of the flap and sealing of all distal re-entry tears can improve long-term outcomes of TEVAR for TBAD.